2004
DOI: 10.1111/j.0956-7976.2004.00662.x
|View full text |Cite
|
Sign up to set email alerts
|

Amygdala Responses to Emotionally Valenced Stimuli in Older and Younger Adults

Abstract: As they age, adults experience less negative emotion, come to pay less attention to negative than to positive emotional stimuli, and become less likely to remember negative than positive emotional materials. This profile of findings suggests that, with age, the amygdala may show decreased reactivity to negative information while maintaining or increasing its reactivity to positive information. We used event-related functional magnetic resonance imaging to assess whether amygdala activation in response to posit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

39
339
7
9

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 482 publications
(405 citation statements)
references
References 40 publications
39
339
7
9
Order By: Relevance
“…This finding suggests that, in contrast to adults, young children may find smiling expressions -considered to be rewarding in their own right -to be more salient than angry ones. This interpretation is consistent with a well-documented positivity bias in older adults [45], accompanied by preferential amygdala activation for positive versus negative stimuli [46]. Thus, the relative salience of positive and negative facial expressions may be different at different developmental stages, suggesting normative developmental changes in affect-biased attention, or what individuals are predisposed to attend to, with both young children and older adults showing evidence of a positivity bias relative to young adults.…”
Section: Affective Tuning Can Shift With Age and Contextsupporting
confidence: 83%
“…This finding suggests that, in contrast to adults, young children may find smiling expressions -considered to be rewarding in their own right -to be more salient than angry ones. This interpretation is consistent with a well-documented positivity bias in older adults [45], accompanied by preferential amygdala activation for positive versus negative stimuli [46]. Thus, the relative salience of positive and negative facial expressions may be different at different developmental stages, suggesting normative developmental changes in affect-biased attention, or what individuals are predisposed to attend to, with both young children and older adults showing evidence of a positivity bias relative to young adults.…”
Section: Affective Tuning Can Shift With Age and Contextsupporting
confidence: 83%
“…(2007) have shown that brain reactivity to negative emotional input decreased linearly with age, while it remained stable for positive input. Finally, an age-related reduced reactivity of the amygdala has been described for negative facial expressions and pictures, but not for positive ones (e.g., Gunning-Dixon et al, 2003;Iidaka et al, 2002;Mather et al, 2004). It is therefore possible that the age-related changes in motivation towards positive input and the bias to positivity, which appear to be linked with changes in brain function, underlie the pattern of results reported here.…”
Section: Explanatory Hypothesesmentioning
confidence: 46%
“…Converging evidence supports the link between this motivational shift and age-related changes in how we recognize and process emotional stimuli (GunningDixon et al, 2003;Iidaka et al, 2002;Jacques, Dolcos, & Cabeza, 2008;Kisley, Wood, & Burrows, 2007;Mather et al, 2004;Williams et al, 2006). For instance, Williams and colleagues (2006) analyzed the recognition of fearful, happy and neutral facial expressions from 12 to 79 years of age using behavioral, neurophysiological and neuroimaging methods.…”
Section: Emotion Recognition In Music Changes Across the Adult Life Spanmentioning
confidence: 98%
“…While amygdala and fusiform gyrus activity decreases, prefrontal activity increases in healthy older men and women (460 years) in comparison to young adults (o30 years) (Iidaka et al, 2002;Gunning-Dixon et al, 2003;Mather et al, 2004;Tessitore et al, 2005). However, to our knowledge, amygdala reactivity during midlife has not been investigated previously.…”
Section: Discussionmentioning
confidence: 86%